Comparative Study of Hyperbaric Ropivcaine and Hyperbaric Bupivacaine for Spinal Anaesthesia - Vidyalakshmi; Balbir Singh Sekhon; Mandeep Kaur; Rakesh Sadhu; Namita (Academia Anesthesiologica International, 2022)
Background: Ropivacaine is a newly introduced amide local anaesthetic. Hyperbaric Ropivacaine solutions are known to produce reliable spinal anaesthesia, having good motor sensory dissociation. Ropivacaine is 40 % less potent than Bupivacaine and less cardiotoxic. AIM: To evaluate and compare the clinical efficacy of 0.5% Hyperbaric solution of Ropivacaine versus Bupivacaine in terms of characteristic of spinal blockade, hemodynamic stability, intraoperative and postoperative side effects and recovery profile. Subjects and Methods: The study enrolled 100 patients of either sex, ASA grade I and II randomly allocated into two groups Group B (Bupivacaine) and Group R (Ropivacaine). Group B received 3 ml of 0.5 % Hyperbaric Bupivacaine and Group R received 3 ml of 0.5 % Hyperbaric Ropivacaine. Onset and duration of sensory blockade assessed by pin prick method. Onset and duration of motor blockade assessed by modified Bromage scale. Various parameters of subarachnoid blockade, hemodynamic variables, recovery, quality of anaesthesia, recovery and side effects were assessed. Results: Hyperbaric Ropivacaine group had late onset of sensory, motor blockade and lesser degree of motor blockade, shorter total duration of motor and sensory blockade with early regression. It had good hemodynamic profile. Patients in this group passed urine sooner. Patients had early mobilization in Ropivacaine group. Conclusion: Ropivacaine provided a reliable spinal anaesthesia with early recovery profile and lesser side effects compared to Bupivacaine and hence Ropivacaine may be a better option for day care setting.